An approach to the selection of target reliability index of Cable-stayed bridge's main girder based on optimal structural parameter ratio from cost-benefit analysis. (December 2020) - Zhang, Zhenhao; Li, Wenbiao; Ding, Zhouxiang; Wu, Xueyan
Abstract: A reasonable value of target reliability index is vital for long-span cable-stayed bridges. However, there are few methods to determine the reasonable target reliability index for long-span cable-stayed bridges. In this work, an original approach to solve this problem is developed. In this approach, a concept of optimal structural parameter ratio is presented from the perspective of cost-benefit. Determination of structural target reliability index should meet the requirements of safety and economy. This approach includes two parts. First, based on the statistical parameters of load and resistance of the cable-stayed bridge's main girder and the most unfavourable bending moments obtained by finite element analysis, the structural reliability index was calculated by the JC method. Second, the reliability indexes with different structural parameter ratios were calculated, and the relational expression between the reliability index and structural parameter ratio was obtained by data fitting. Then the optimal structural parameter ratio was calculated from the perspective of cost-benefit. Finally, by substituting the optimal structural parameter ratio into the relational expression between the reliability index and structural parameter ratio, the optimal reliability index can be obtained. The optimal reliability index corresponding to the optimal structural parameter ratio can be regarded as the target reliability index.